Optimization of Yellowfin Tuna Production in Ternate Island Waters Using Geographic Information System - Mustafa, Hajrul; Tangke, Umar; Darmawaty, Darmawaty (JURNAL BIOSAINSTEK, 2024)
This research was conducted from July to September 2023, with the aim of analyzing the relationship between oceanographic parameters and yellowfin tuna catch. The use of experimental fishing method with regression analysis and geographic information system is expected to answer the research objectives. Based on the results of the study, it was found that simultaneously oceanographic conditions have a significant effect on the catch of yellowfin tuna in Ternate Island waters with a calculated F value of 12,449 and a significance of 0.000, then with the backward method it was found that individually only sea surface temperature and chlorophyll-a concentration parameters were closely related to yellowfin tuna catches with a coefficient of determination (r2) value of 0.581 and 0.461, respectively. It is necessary to conduct further research with different fishing locations in order to determine the potential of fisheries, especially yellowfin tuna.